Analysis of the Genetic Diversity in Indian Mustard (Brassica juncea L. Czern&Coss) Genotypes - Chauhan, Rahul Singh; Kumar, Mukesh; Kumar, Shubham; Tiwari, Mayank; Tiwari, Utkarsh (International Journal of Bio-resource and Stress Management, 2023)
A study was undertaken during the rabi season (October, 2021 to March, 2022) at the crop research center Sardar Vallabhbhai Patel University of Agriculture and Technology Meerut, Uttar Pradesh, India to find out the genetic divergence in 40 genotypes of Indian mustard using the D2 statistical approach. Forty (40) diverse genotypes of Indian mustard were examined for genetic divergence using a randomized complete block design (RCBD) with three replications. Observations were recorded on various 14 characters viz; days to 50% flowering, days to maturity, plant height (cm), number of primary branches plant-1, number of secondary branches plant-1, siliquae on main axis, length of main axis (cm), siliqua length (cm), number of seeds siliqua-1, 1000 seed weight (g), biological yield plant-1 (g), harvest index (%), oil content (%) and seed yield plant-1 (g). Mahalanobis D2 statistics were applied to the analysis of genetic divergence. Based on D2 values 40 genotypes were grouped into 5 clusters, maximum genotypes eleven obtained in cluster IV after that cluster I with nine genotypes, cluster V with eight genotypes, cluster III with seven genotypes and cluster II with five genotypes. The maximum intra-cluster was in cluster IV. The maximum inter-cluster distance was revealed between cluster II and V. It is clearly indicated that the genotypes included in this cluster are having a wide spectrum of genetic diversity. According to the role of many traits under examination in the manifestation of genetic divergence, plant height had the biggest contribution to divergence.